Cuidados de enfermería en paciente geriátrico con úlceras isquémicas - Rivera Cedeño , Yander Alexander (2024)
The purpose of this case study was to comprehensively analyze nursing care in a geriatric patient with ischemic ulcers, covering key aspects of care such as continuous monitoring of the ulcers and evaluation of results in terms of healing. The patient was admitted due to a simple diabetic decompensation, characterized by hyperglycemia, in addition to severe pain in the left lower limb, having as comorbidities present type 2 diabetes mellitus and arterial hypertension. Physical examination revealed the presence of necrotic plaque in the left lower limb with marked fetidness and serohematic secretion. Through the comprehensive assessment it was identified that the patient was concerned about her state of health, metabolic nutritional problems due to unstable capillary glycemia and skin lesions, limitations in physical activity due to pain and presence of ulcers. Through the care plan it was established by means of precise diagnostic analyses, the expected results and the respective interventions that were mainly oriented to pain control, glycemia level, management of arterial insufficiency, wound care: absence of scarring, infection control, among others. However, the efficacy of treatment in the ulcer bed was compromised by insufficient blood flow, which exacerbated the infection and led to a radical and irreversible therapeutic decision to prevent serious complications. This case highlights the importance of a multidisciplinary and proactive approach in the management of patients with ischemic ulcers, underlining the need for therapeutic strategies and continuous surveillance to optimize clinical outcomes and improve quality of life.